Fly ash unfired ceramsite and preparation method thereof
Through alkali solution pretreatment, calcium excitation, water stirring and secondary pelletization processes, combined with composite maintenance, the problems of insufficient activity and low granulation efficiency of fly ash ceramic granules are solved, and high strength, stability and low Cost preparation of fly ash without burning ceratops, suitable for lightweight concrete.
Patent Information
- Application Number
- CN202411325351.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-23
AI Technical Summary
In the existing fly ash ceramic preparation technology, fly ash activity is insufficient, the granulation process is complex and difficult to control accurately. The water addition method leads to material adhesion and unstable strength of the ceramic, which affects its application in the concrete field.
After alkali solution pretreatment, calcium substances are added to stimulate fly ash, the water consumption is accurately controlled by adding water and stirring, and secondary pelletization is carried out to build a core-shell structure, combining a composite method of natural, constant temperature and humidity and steam maintenance.
It significantly improves the mechanical properties of fly ash ceramic particles, simplifies the granulation process, reduces the amount of cement and curing time, improves the structural stability and durability of the ceramic particles, and is suitable for lightweight structural concrete.
Smart Images

Figure CN119161160A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of unburned ceramsite preparation, and particularly relates to fly ash unburned ceramsite and a preparation method thereof. Background Art
[0002] Fly ash is fine ash captured from coal-fired flue gas. It is a solid waste discharged by thermal power plants and has become the largest single source of solid pollution in my country. Its annual emissions are increasing year by year. However, the overall utilization rate of fly ash is still at a low level. At present, the main utilization methods of fly ash include cement, concrete and building materials production. With the continuous improvement of science and technology, building materials have developed towards lightweight and high performance. Under this trend, the development of expanded clay has emerged. Unburned fly ash expanded clay refers to the use of fly ash as the main raw material without roasting in the preparation process of expanded clay. Admixtures and binders are added to make mixed granules. It is obtained by natural curing, steam curing or autoclaving. Its strength development mechanism is that through chemical excitation, after the curing process, the active oxides such as SiO2 and Al2O3 in the fly ash react with alkaline substances and react with Ca 2+ The reaction generates calcium silicate hydrate (CSH) and calcium aluminate hydrate (CAH) hydraulic cementitious products, which improve the mechanical properties of ceramsite. Compared with sintered fly ash ceramsite, it has high raw material utilization, simple process, no need for large equipment, green and environmental protection, has a broader development prospect, and is in line with the national circular economy development.
[0003] Therefore, the degree of activation of fly ash volcanic ash activity is particularly critical. The present invention shows that a single alkaline solution pretreatment such as NaOH and a single addition of calcium such as Ca(OH)2 or gypsum cannot enhance the strength of ceramsite. The fly ash activation method of adding calcium after alkaline solution pretreatment can effectively improve the activity of fly ash, and the addition of calcium can cause the system to undergo silicon-calcium reaction, significantly enhancing the mechanical properties of fly ash ceramsite. At the same time, the fly ash unburned ceramsite is subjected to a secondary pelletization process to construct a core-shell structure ceramsite, which can greatly improve its structural stability. On the other hand, accurate control of water consumption is a prerequisite for forming fly ash pellets of uniform size. The optimal amount of water added should be able to fill all the gaps between the fly ash particles, but at the same time will not form a water film on the surface of the pellets. At present, the way of adding water in the granulation process of fly ash ceramsite is often to spray mist water on the dry material during the rotation of the ball forming disk. The process is complicated and difficult to control, and it is easy to cause the material to adhere to the ball forming disk, reducing the utilization rate of raw materials and other problems. In addition, the reaction in the fly ash balls is a slow and continuous process, which is often affected by external curing conditions such as temperature, humidity and pressure. Therefore, the composite curing method of the present invention combines multiple curing systems. Compared with a single form of curing, it can quickly improve the strength of fly ash ceramsite, reduce the curing age and reduce costs, and has good application advantages.
[0004] The existing fly ash unburned ceramsite preparation technology is generally as follows: the dried fly ash is mixed with a certain amount of cement, quicklime or water glass powder, and then put into a stirring device such as a mixer for stirring. The material obtained after stirring evenly is put into a granulating device such as a disc granulator, and the disc angle and speed are set. After the granulator is started and the speed is constant and the rolling state of the internal material tends to be stable, water is slowly sprinkled on the material, and the single water spraying time and water spraying interval are fixed. After 1~2 minutes, the granulation situation is observed, and the spherical particles are taken out for curing. After a certain age, fly ash unburned ceramsite is obtained. Specific description: 1. The above fly ash types are mostly Grade I to II fly ash, cement is ordinary Portland cement, the model is mostly P.O52.5 or PO 42.5, the main component of quicklime is CaO, which is mostly ordinary commercial quicklime or CaO chemical reagent, and the main component of water glass is Na2SiO3, which is often ordinary commercial water glass or Na2SiO3 chemical reagent.
[0005] 2. Most of the above-mentioned disc granulators are common commercial granulating equipment. The diameter of the granulator ranges from 400 to 800 mm, the height of the baffle ranges from 100 to 350 mm, the inclination angle of the disc is generally 35° to 55°, and the speed is 30 to 35 r / min (revolutions per minute).
[0006] 3. The above-mentioned watering method is generally to add water from a spray bottle, which is often set in a shower shape or cluster shape. One spray lasts about 1 second, and each spray is 5 to 10 seconds apart and lasts for 1 to 2 minutes. The amount of water added is generally 10% to 35% (total material mass fraction).
[0007] 4. The duration of the above granulation is generally 8 to 20 minutes, and curing is carried out directly after the granulation is completed.
[0008] 5. Most of the above maintenance methods are natural maintenance, with an age of 28 days.
[0009] 6. The above fly ash unburned ceramsite preparation technology is specifically: (1) After drying to constant weight, weigh the raw materials according to the proportion of each ingredient; (2) placing the raw materials in a stirring device such as a mixer and stirring for 60 seconds to obtain a uniform dry mixed material; (3) Pour the dry mixed material into a granulation device such as a disc granulator. Taking the disc granulator as an example, set the disc inclination angle to 35°~55°, the speed to 30~35r / min, and the baffle height to 100~350mm; (4) Start the disc granulator. After 30 seconds, when the speed is constant and the rolling state of the internal material tends to be stable, use a spray pot to slowly spray water on the material. The spray pot is set to a shower shape or a cluster shape. The water spray lasts for about 1 second each time. The interval between each spray is 5 to 10 seconds and lasts for 1 to 2 minutes. The amount of water added is generally 10% to 35% (total material mass fraction). (5) After the water spraying continues for 1 to 2 minutes, the granulation condition is observed, the spherical particles are taken out, and the water spraying is continued in the above-mentioned water adding method to continuously take out the ceramsite raw material balls. The granulation time is about 8 to 20 minutes, until the remaining materials can no longer be granulated. The obtained ceramsite raw material balls are cured. The natural curing is to place them in an indoor environment for 28 days. The steam curing is to place the ceramsite raw material balls in a steam curing box for 6 to 24 hours after pretreatment such as standing or drying at room temperature. The temperature is generally 60 to 90°C. Finally, fly ash unfired ceramsite is obtained.
[0010] Disadvantages of existing technology: (1) In the existing fly ash unfired ceramsite preparation technology, the fly ash activity is not fully activated, and the alkaline activator is usually a single water glass or quicklime, etc., which leads to insufficient internal reaction products of fly ash unfired ceramsite, reducing its mechanical properties. Increasing the amount of alkaline activator will increase the preparation cost. In addition, in the traditional fly ash unfired ceramsite preparation technology, in order to improve the comprehensive performance of ceramsite, a large amount of cement is often used as a ceramsite binder, with an amount of 20%~50% (total dry material mass fraction), which is costly and not conducive to the consumption of fly ash.
[0011] (2) In the existing fly ash unburned ceramsite preparation process, the traditional watering process of adding water with a spray pot is relatively complicated, and the amount of water added is difficult to accurately control, resulting in large errors. In addition, adding water with a spray pot easily causes the material to adhere to the ball-forming plate, reducing the utilization rate of the raw materials, and the water content of the ceramsite raw material balls formed in a single time is often different from the optimal water content, resulting in a large dispersion of the ceramsite particle size and strength from the set value.
[0012] (3) In the existing fly ash unburned expanded clay performance enhancement process, the secondary pelletization process is relatively complicated. The expanded clay matrix is often cured for 3 to 7 days before constructing a core-shell structure, and the proportion of cement in the shell material is relatively high.
[0013] (4) The existing fly ash unburned ceramsite curing stage is generally natural curing or steam curing, which has a long curing period or high cost. During the 28-day natural curing, the temperature and humidity that significantly affect the degree of internal reaction of the ceramsite cannot be kept constant, and before steam curing, the ceramsite raw material balls need to be pretreated. Moreover, the long-term steam curing can easily cause the ceramsite to be subjected to continuous thermal shock, which will damage its surface and reduce its mechanical properties. Summary of the invention
[0014] The purpose of the present invention is to provide a fly ash unfired ceramsite and a preparation method thereof, which solves the problem that the fly ash is insufficiently active, resulting in a small number of reaction products and low strength of the fly ash unfired ceramsite, and solves the technical problem that the traditional water addition method of granulation is difficult to accurately control, resulting in low efficiency of fly ash unfired ceramsite granulation. In addition, the problem of poor initial structural stability and durability of conventional unfired ceramsite is solved, thereby solving the problem that the fly ash unfired ceramsite becomes a weak point in its mechanical properties when applied to the field of concrete.
[0015] To achieve the above object, the present invention adopts the following technical solutions: A method for preparing fly ash unfired ceramsite: the fly ash unfired ceramsite is granulated to obtain a ceramsite matrix, which is then subjected to secondary pelletization to construct a shell structure, and is obtained after a composite curing method; the ceramsite matrix is prepared from fly ash, cement, gypsum, an alkali activator, and water, wherein the fly ash accounts for 86.2wt% to 90.9wt% of the total dry material, cement accounts for 10% of the fly ash mass, gypsum accounts for 2% of the fly ash mass, the alkali activator accounts for 2% to 5% of the fly ash mass, and the amount of water added is 25% of the fly ash mass; the shell is made of fly ash and cement; and the total shell material is 10% of the fly ash mass used in the ceramsite matrix.
[0016] Preferably, the granulation equipment is a disc granulator with a diameter of 600 mm.
[0017] Preferably, the fly ash is Class II F, the cement is ordinary Portland cement, model PO 42.5, and the gypsum is dihydrate gypsum.
[0018] Preferably, the alkaline activator is composed of calcium oxide, sodium silicate and sodium hydroxide, all of which are pure chemical reagents. The amount of calcium oxide is 2% to 3% of the mass of fly ash, the amount of sodium silicate is 0.25% to 1% of the mass of fly ash, and the amount of sodium hydroxide is 0.25% to 1% of the mass of fly ash. The fly ash used in the shell accounts for 90wt% of the shell material, and cement accounts for 10wt% of the shell material.
[0019] Preferably, the water is added after the materials are dry-mixed evenly.
[0020] Preferably, the composite curing is natural curing combined with constant temperature and humidity curing and steam curing, which are performed in sequence, and the three curing times are all 12 hours.
[0021] A method for preparing fly ash unburned ceramsite comprises the following steps: (1) Dry the fly ash to a constant weight and weigh each raw material according to the ratio; (2) Pour fly ash, cement and gypsum into a mixer and stir for 60 seconds to obtain a uniform dry mixed material; (3) Pour sodium hydroxide and sodium silicate into water, stir clockwise until completely dissolved in water, then pour the solution into the dry mixed material, stir for 90 seconds, obtain a wet mixed material, add calcium oxide, and continue stirring for 60 seconds; (4) Pour all materials into the disc granulator, set the disc inclination angle to 50°, the speed to 60r / min, and the baffle height to 30~100mm; (5) After 60 seconds of granulation, a ceramsite matrix is obtained, and the shell material is sprinkled on the surface of the ceramsite matrix, which is rotated in the granulator for 30 seconds for secondary pelletization and then taken out; by continuously lowering the baffle height (from 100 mm to 30 mm), the granulation-shell material sprinkling-secondary pelletization steps are repeated, and the granulation and secondary pelletization steps are continuously performed until the granulation is completed. The entire granulation process lasts for 15 minutes; (6) All the ceramsite after secondary pelletization is placed in an indoor environment for natural curing for 12 hours, and then moved into a constant temperature and humidity curing room with a temperature of 20±2°C and a relative humidity of ≥95%. After curing for 12 hours, it is placed in a steam curing box at a temperature of 90°C for 12 hours, and then allowed to stand at room temperature to obtain fly ash unfired ceramsite.
[0022] The key points of the present invention are: (1) The water adding method adopted in the present invention is to add water after the dry materials are evenly stirred, which is different from the water adding method of a spray pot in the conventional granulation process, which is quite special.
[0023] (2) The present invention uses a method of pre-treating fly ash with sodium silicate and sodium hydroxide alkaline solution and then adding calcium substances (calcium oxide) to activate fly ash, which is different from the traditional fly ash using a single type of activator. In addition, the amount of cement used in the present invention is 10% of the mass fraction of fly ash, which is significantly lower than the traditional cement content.
[0024] (3) The present invention adopts a process of immediately performing secondary pelletization on fly ash unfired ceramsite raw material balls after forming to construct a core-shell structure, which is different from the conventional fly ash unfired ceramsite matrix that is cured before performing secondary pelletization.
[0025] (4) The present invention adopts a composite curing method to cure the fly ash unfired ceramsite, which is different from the single curing method of the traditional fly ash unfired ceramsite.
[0026] The advantages of the present invention are: (1) The present invention avoids the problem of adding water in a watering can in the traditional granulation process, which is more likely to cause the material to adhere to the ball-forming plate and reduce the utilization rate of raw materials. The present invention accurately controls the amount of water by adding water and stirring, and no water needs to be added in the subsequent granulation process, thereby increasing the proportion of fly ash particles in a capillary state during the granulation process, avoiding the problem of difficulty in granulation and molding when the amount of water is insufficient, and when the amount of water is too much, the excess water will cause the particles to become larger, causing the ceramsite spheres to collapse and deform, and adversely affecting the early strength of the ceramsite. In addition, the water-adding method provided by the present invention can be used as a fly ash alkaline solution pretreatment process, and the fly ash can be activated before granulation.
[0027] (2) The present invention avoids the problem that insufficient activation of fly ash leads to less internal products of fly ash unfired ceramsite, low strength, high water absorption, etc. The present invention adopts the method of adding calcium substances after alkaline solution pretreatment to make fly ash in OH - Under the action of ions, the network structure of the glass surface is destroyed, the degree of polymerization of the network aggregate is greatly reduced, and the active oxides of SiO2 and Al2O3 are dissolved and precipitated, which significantly stimulates the volcanic ash activity of fly ash. The addition of calcium causes the active oxides to react chemically to generate gelling substances such as CSH and C-(A)-SH and products such as ettringite, thereby improving the mechanical properties of expanded clay.
[0028] (3) The core-shell structure ceramsite constructed by the present invention has the characteristics of simple process, low cement dosage and excellent physical properties. At the same time, there is no need to perform secondary pelletization after curing the ceramsite matrix, which saves time and cost. In addition, the composite curing process adopted by the present invention significantly shortens the curing age. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The present invention is a schematic diagram of the preparation process of fly ash unburned ceramsite. DETAILED DESCRIPTION
[0030] In order to make the above features and advantages of the present invention more clearly understood, the following embodiments are given for detailed description. The methods of the present invention are all conventional methods in the art unless otherwise specified.
[0031] The present embodiment provides a fly ash unfired ceramsite and a preparation method thereof, wherein the fly ash unfired ceramsite is granulated to obtain a ceramsite matrix, and then a shell structure is constructed by secondary pelletization, and then a composite curing method is adopted to obtain the ceramsite matrix; the ceramsite matrix is prepared from fly ash, cement, gypsum, alkali activator, and water, wherein the fly ash is Class II F, accounting for 86.2wt% to 90.9wt% of the total dry material, and the cement type is PO 42.5, and the amount is 10% of the fly ash mass. The gypsum is dihydrate gypsum, and the amount is 2% of the fly ash mass. The alkali activator is composed of calcium oxide, sodium silicate, and sodium hydroxide, all of which are pure chemical reagents, the amount of calcium oxide is 2% to 3% of the fly ash mass, the amount of sodium silicate is 0.25% to 1% of the fly ash mass, and the amount of sodium hydroxide is 0.25% to 1% of the fly ash mass; the amount of water added is 25% of the fly ash mass.
[0032] The fly ash used in the shell accounts for 90wt% of the shell material, and the cement accounts for 10wt% of the shell material.
[0033] The water is added after the materials are dry-mixed evenly.
[0034] The secondary pelletization is to sprinkle fly ash and cement immediately after granulation to construct core-shell structure ceramsite.
[0035] The composite curing method includes natural curing + constant temperature and humidity curing + steam curing.
[0036] Comparative Example 1 (1) Weigh 3000 parts of Class II F fly ash dried to constant weight, 600 parts of PO 42.5 ordinary Portland cement, 60 parts of dihydrate gypsum, 90 parts of calcium oxide chemical reagent (analytical grade, CaO content ≥ 98%), and 700 parts of water according to mass proportions, pour the water into a spray pot and set aside; (2) The weighed fly ash, cement, gypsum and calcium oxide are placed in a mixer and stirred for 60 seconds to obtain a uniform dry mixed material; (3) Pour the dry mixed material into the disc granulator, set the disc inclination angle to 45°, the speed to 30 r / min, and the baffle height to 150 mm; (4) After starting the disc granulator for 30 seconds, use a spray pot to slowly spray water on the material. The spray pot is set to a shower shape, spraying water for 1 second each time, with an interval of 5 seconds between each spraying, and continue for 90 seconds; (5) Observe the granulation process, take out the spherical particles, continue to spray water in the above-mentioned water adding method, and continuously take out the expanded clay raw material balls. The granulation time lasts for 15 minutes until the remaining materials can no longer be granulated. Place the prepared expanded clay raw material balls in an indoor environment for natural curing for 28 days.
[0037] Comparative Example 2 (1) Weigh 3000 parts of Class II F fly ash dried to constant weight, 600 parts of PO 42.5 ordinary Portland cement, 60 parts of dihydrate gypsum, 90 parts of calcium oxide chemical reagent (analytical grade, CaO content ≥ 98%), and 700 parts of water according to mass proportions, pour the water into a spray pot and set aside; (2) The weighed fly ash, cement, gypsum and calcium oxide are placed in a mixer and stirred for 60 seconds to obtain a uniform dry mixed material; (3) Pour the dry mixed material into the disc granulator, set the disc inclination angle to 45°, the speed to 30 r / min, and the baffle height to 150 mm; (4) After starting the disc granulator for 30 seconds, use a spray pot to slowly spray water on the material. The spray pot is set to a shower shape, spraying water for 1 second each time, with an interval of 5 seconds between each spraying, and continue for 90 seconds; (5) Observe the granulation situation, take out the spherical particles, continue to spray water in the above-mentioned water adding method, and continuously take out the expanded clay raw material balls. The granulation time continues for 15 minutes until the remaining materials can no longer be granulated. The prepared expanded clay raw material balls are placed in an indoor environment for 6 hours, and then placed in a 90°C steam curing box for 24 hours.
[0038] Comparative Example 3 (1) Weigh 3000 parts of Class II F fly ash dried to constant weight, 600 parts of PO 42.5 ordinary Portland cement, 60 parts of dihydrate gypsum, 75 parts of sodium silicate chemical reagent (analytical grade, Na2SiO3 ≥ 98%), and 700 parts of water according to mass proportions, place the sodium silicate in the water and stir evenly, pour the sodium silicate solution into a spray pot and set aside; (2) The weighed fly ash, cement and gypsum are placed in a mixer and stirred for 60 seconds to obtain a uniform dry mixed material; (3) Pour the dry mixed material into the disc granulator, set the disc inclination angle to 45°, the speed to 30 r / min, and the baffle height to 150 mm; (4) After starting the disc granulator for 30 seconds, use a spray pot to slowly spray the sodium silicate solution on the material. The spray pot is set to a shower shape, spraying water for 1 second each time, with an interval of 5 seconds between each spraying, and continuing for 90 seconds; (5) Observe the granulation process, take out the spherical particles, continue to spray water in the above-mentioned water adding method, and continuously take out the expanded clay raw material balls. The granulation time lasts for 15 minutes until the remaining materials can no longer be granulated. Place the prepared expanded clay raw material balls in an indoor environment for natural curing for 28 days.
[0039] Comparative Example 4 (1) Weigh 3000 parts of Class II F fly ash dried to constant weight, 600 parts of PO 42.5 ordinary Portland cement, 60 parts of dihydrate gypsum, 75 parts of sodium silicate chemical reagent (analytical grade, Na2SiO3 ≥ 98%), and 700 parts of water according to mass proportions, place the sodium silicate in the water and stir evenly, pour the sodium silicate solution into a spray pot and set aside; (2) The weighed fly ash, cement and gypsum are placed in a mixer and stirred for 60 seconds to obtain a uniform dry mixed material; (3) Pour the dry mixed material into the disc granulator, set the disc inclination angle to 45°, the speed to 30 r / min, and the baffle height to 150 mm; (4) After starting the disc granulator for 30 seconds, use a spray pot to slowly spray the sodium silicate solution on the material. The spray pot is set to a shower shape, spraying water for 1 second each time, with an interval of 5 seconds between each spraying, and continuing for 90 seconds; (5) Observe the granulation situation, take out the spherical particles, continue to spray water in the above-mentioned water adding method, and continuously take out the expanded clay raw material balls. The granulation time continues for 15 minutes until the remaining materials can no longer be granulated. The prepared expanded clay raw material balls are placed in an indoor environment for 6 hours, and then placed in a 90°C steam curing box for 24 hours.
[0040] Example 1 (1) Weigh 3000 parts of Class F II fly ash dried to constant weight, 300 parts of PO 42.5 ordinary Portland cement, 60 parts of dihydrate gypsum, 60 parts of calcium oxide (analytical grade), 7.5 parts of sodium silicate powder (analytical grade), and 750 parts of water according to mass proportions; weigh 270 parts of Class F II fly ash and 30 parts of PO 42.5 ordinary Portland cement as shell materials, and set aside; (2) Pour fly ash, cement and gypsum into a mixer and stir for 60 seconds to obtain a uniform dry mixed material. (3) Pour the weighed sodium silicate powder into water and stir continuously in a clockwise direction until it is completely dissolved in water. Then pour the solution into the dry mixed material and stir for 90 seconds to obtain a wet mixed material. Add the weighed calcium oxide and continue stirring for 60 seconds.
[0041] (4) Pour all the materials into the disc granulator, set the disc inclination angle to 50°, the speed to 60r / min, and the baffle height to 30~100mm.
[0042] (5) Place the weighed shell material in a small blender and stir for 60 seconds; (6) After 60 seconds of granulation, the ceramsite matrix is obtained, and the shell material is coated on the surface of the formed ceramsite matrix. The ceramsite matrix is rotated in the granulator for 30 seconds for secondary pelletization and then taken out; by continuously lowering the baffle height (from 100 mm to 30 mm), the granulation-shell material-secondary pelletization steps are repeated, and the granulation and secondary pelletization steps are continuously performed until the granulation is completed. The entire granulation process lasts for 15 minutes.
[0043] (7) All the ceramsite after secondary pelletization is placed in an indoor environment for natural curing for 12 hours, and then moved into a constant temperature and humidity curing room with a temperature of 20±2°C and a relative humidity ≥95%. After curing for 12 hours, it is placed in a steam curing box at a temperature of 90°C for 12 hours, and then allowed to stand at room temperature to obtain fly ash unfired ceramsite.
[0044] Example 2 (1) Weigh 3000 parts of Class F II fly ash dried to constant weight, 300 parts of PO 42.5 ordinary Portland cement, 60 parts of dihydrate gypsum, 60 parts of calcium oxide (analytical grade), 15 parts of sodium silicate powder (analytical grade), and 750 parts of water according to mass proportions; weigh 270 parts of Class F II fly ash and 30 parts of PO 42.5 ordinary Portland cement as shell materials, and set aside; (2) Pour fly ash, cement and gypsum into a mixer and stir for 60 seconds to obtain a uniform dry mixed material. (3) Pour the weighed sodium silicate powder into water and stir continuously in a clockwise direction until it is completely dissolved in water. Then pour the solution into the dry mixed material and stir for 90 seconds to obtain a wet mixed material. Add the weighed calcium oxide and continue stirring for 60 seconds.
[0045] (4) Pour all the materials into the disc granulator, set the disc inclination angle to 50°, the speed to 60r / min, and the baffle height to 30~100mm.
[0046] (5) Place the weighed shell material in a small blender and stir for 60 seconds; (6) After 60 seconds of granulation, the ceramsite matrix is obtained, and the shell material is coated on the surface of the formed ceramsite matrix. The ceramsite matrix is rotated in the granulator for 30 seconds for secondary pelletization and then taken out; by continuously lowering the baffle height (from 100 mm to 30 mm), the granulation-shell material-secondary pelletization steps are repeated, and the granulation and secondary pelletization steps are continuously performed until the granulation is completed. The entire granulation process lasts for 15 minutes.
[0047] (7) All the ceramsite after secondary pelletization is placed in an indoor environment for natural curing for 12 hours, and then moved into a constant temperature and humidity curing room with a temperature of 20±2°C and a relative humidity ≥95%. After curing for 12 hours, it is placed in a steam curing box at a temperature of 90°C for 12 hours, and then allowed to stand at room temperature to obtain fly ash unfired ceramsite.
[0048] Example 3 (1) Weigh 3000 parts of Class F II fly ash dried to constant weight, 300 parts of PO 42.5 ordinary Portland cement, 60 parts of dihydrate gypsum, 60 parts of calcium oxide (analytical grade), 22.5 parts of sodium silicate powder (analytical grade), and 750 parts of water according to mass proportions; weigh 270 parts of Class F II fly ash and 30 parts of PO 42.5 ordinary Portland cement as shell materials, and set aside; (2) Pour fly ash, cement and gypsum into a mixer and stir for 60 seconds to obtain a uniform dry mixed material. (3) Pour the weighed sodium silicate powder into water and stir continuously in a clockwise direction until it is completely dissolved in water. Then pour the solution into the dry mixed material and stir for 90 seconds to obtain a wet mixed material. Add the weighed calcium oxide and continue stirring for 60 seconds.
[0049] (4) Pour all the materials into the disc granulator, set the disc inclination angle to 50°, the speed to 60r / min, and the baffle height to 30~100mm.
[0050] (5) Place the weighed shell material in a small blender and stir for 60 seconds; (6) After 60 seconds of granulation, the ceramsite matrix is obtained, and the shell material is coated on the surface of the formed ceramsite matrix. The ceramsite matrix is rotated in the granulator for 30 seconds for secondary pelletization and then taken out; by continuously lowering the baffle height (from 100 mm to 30 mm), the granulation-shell material-secondary pelletization steps are repeated, and the granulation and secondary pelletization steps are continuously performed until the granulation is completed. The entire granulation process lasts for 15 minutes.
[0051] (7) All the ceramsite after secondary pelletization is placed in an indoor environment for natural curing for 12 hours, and then moved into a constant temperature and humidity curing room with a temperature of 20±2°C and a relative humidity ≥95%. After curing for 12 hours, it is placed in a steam curing box at a temperature of 90°C for 12 hours, and then allowed to stand at room temperature to obtain fly ash unfired ceramsite.
[0052] Example 4 (1) Weigh 3000 parts of Class F II fly ash dried to constant weight, 300 parts of PO 42.5 ordinary Portland cement, 60 parts of dihydrate gypsum, 60 parts of calcium oxide (analytical grade), 30 parts of sodium silicate powder (analytical grade), and 750 parts of water according to mass proportions; weigh 270 parts of Class F II fly ash and 30 parts of PO 42.5 ordinary Portland cement as shell materials, and set aside; (2) Pour fly ash, cement and gypsum into a mixer and stir for 60 seconds to obtain a uniform dry mixed material. (3) Pour the weighed sodium silicate powder into water and stir continuously in a clockwise direction until it is completely dissolved in water. Then pour the solution into the dry mixed material and stir for 90 seconds to obtain a wet mixed material. Add the weighed calcium oxide and continue stirring for 60 seconds.
[0053] (4) Pour all the materials into the disc granulator, set the disc inclination angle to 50°, the speed to 60r / min, and the baffle height to 30~100mm.
[0054] (5) Place the weighed shell material in a small blender and stir for 60 seconds; (6) After 60 seconds of granulation, the ceramsite matrix is obtained, and the shell material is coated on the surface of the formed ceramsite matrix. The ceramsite matrix is rotated in the granulator for 30 seconds for secondary pelletization and then taken out; by continuously lowering the baffle height (from 100 mm to 30 mm), the granulation-shell material-secondary pelletization steps are repeated, and the granulation and secondary pelletization steps are continuously performed until the granulation is completed. The entire granulation process lasts for 15 minutes.
[0055] (7) All the ceramsite after secondary pelletization is placed in an indoor environment for natural curing for 12 hours, and then moved into a constant temperature and humidity curing room with a temperature of 20±2°C and a relative humidity ≥95%. After curing for 12 hours, it is placed in a steam curing box at a temperature of 90°C for 12 hours, and then allowed to stand at room temperature to obtain fly ash unfired ceramsite.
[0056] Example 5 (1) Weigh 3000 parts of Class F II fly ash dried to constant weight, 300 parts of PO 42.5 ordinary Portland cement, 60 parts of dihydrate gypsum, 75 parts of calcium oxide (analytical grade), 15 parts of sodium silicate powder (analytical grade), and 750 parts of water according to mass proportions; weigh 270 parts of Class F II fly ash and 30 parts of PO 42.5 ordinary Portland cement as shell materials, and set aside; (2) Pour fly ash, cement and gypsum into a mixer and stir for 60 seconds to obtain a uniform dry mixed material. (3) Pour the weighed sodium silicate powder into water and stir continuously in a clockwise direction until it is completely dissolved in water. Then pour the solution into the dry mixed material and stir for 90 seconds to obtain a wet mixed material. Add the weighed calcium oxide and continue stirring for 60 seconds.
[0057] (4) Pour all the materials into the disc granulator, set the disc inclination angle to 50°, the speed to 60r / min, and the baffle height to 30~100mm.
[0058] (5) Place the weighed shell material in a small blender and stir for 60 seconds; (6) After 60 seconds of granulation, the ceramsite matrix is obtained, and the shell material is coated on the surface of the formed ceramsite matrix. The ceramsite matrix is rotated in the granulator for 30 seconds for secondary pelletization and then taken out; by continuously lowering the baffle height (from 100 mm to 30 mm), the granulation-shell material-secondary pelletization steps are repeated, and the granulation and secondary pelletization steps are continuously performed until the granulation is completed. The entire granulation process lasts for 15 minutes.
[0059] (7) All the ceramsite after secondary pelletization is placed in an indoor environment for natural curing for 12 hours, and then moved into a constant temperature and humidity curing room with a temperature of 20±2°C and a relative humidity ≥95%. After curing for 12 hours, it is placed in a steam curing box at a temperature of 90°C for 12 hours, and then allowed to stand at room temperature to obtain fly ash unfired ceramsite.
[0060] Example 6 (1) Weigh 3000 parts of Class F II fly ash dried to constant weight, 300 parts of PO 42.5 ordinary Portland cement, 60 parts of dihydrate gypsum, 90 parts of calcium oxide (analytical grade), 15 parts of sodium silicate powder (analytical grade), and 750 parts of water according to mass proportions; weigh 270 parts of Class F II fly ash and 30 parts of PO 42.5 ordinary Portland cement as shell materials, and set aside; (2) Pour fly ash, cement and gypsum into a mixer and stir for 60 seconds to obtain a uniform dry mixed material. (3) Pour the weighed sodium silicate powder into water and stir continuously in a clockwise direction until it is completely dissolved in water. Then pour the solution into the dry mixed material and stir for 90 seconds to obtain a wet mixed material. Add the weighed calcium oxide and continue stirring for 60 seconds.
[0061] (4) Pour all the materials into the disc granulator, set the disc inclination angle to 50°, the speed to 60r / min, and the baffle height to 30~100mm.
[0062] (5) Place the weighed shell material in a small blender and stir for 60 seconds; (6) After 60 seconds of granulation, the ceramsite matrix is obtained, and the shell material is coated on the surface of the formed ceramsite matrix. The ceramsite matrix is rotated in the granulator for 30 seconds for secondary pelletization and then taken out; by continuously lowering the baffle height (from 100 mm to 30 mm), the granulation-shell material-secondary pelletization steps are repeated, and the granulation and secondary pelletization steps are continuously performed until the granulation is completed. The entire granulation process lasts for 15 minutes.
[0063] (7) All the ceramsite after secondary pelletization is placed in an indoor environment for natural curing for 12 hours, and then moved into a constant temperature and humidity curing room with a temperature of 20±2°C and a relative humidity ≥95%. After curing for 12 hours, it is placed in a steam curing box at a temperature of 90°C for 12 hours, and then allowed to stand at room temperature to obtain fly ash unfired ceramsite.
[0064] Example 7 (1) Weigh 3000 parts of Class F II fly ash dried to constant weight, 300 parts of PO 42.5 ordinary Portland cement, 60 parts of dihydrate gypsum, 75 parts of calcium oxide (analytical grade), 15 parts of sodium silicate powder (analytical grade), 7.5 parts of sodium hydroxide granules (analytical grade), and 750 parts of water according to mass proportions; weigh 270 parts of Class F II fly ash and 30 parts of PO 42.5 ordinary Portland cement as shell materials, and set aside; (2) Pour fly ash, cement and gypsum into a mixer and stir for 60 seconds to obtain a uniform dry mixed material. (3) Pour the weighed sodium silicate powder and sodium hydroxide particles into water and stir continuously in a clockwise direction until they are completely dissolved in water. Then pour the solution into the dry mixed material and stir for 90 seconds to obtain a wet mixed material. Add the weighed calcium oxide and continue stirring for 60 seconds.
[0065] (4) Pour all the materials into the disc granulator, set the disc inclination angle to 50°, the speed to 60r / min, and the baffle height to 30~100mm.
[0066] (5) Place the weighed shell material in a small blender and stir for 60 seconds; (6) After 60 seconds of granulation, the ceramsite matrix is obtained, and the shell material is coated on the surface of the formed ceramsite matrix. The ceramsite matrix is rotated in the granulator for 30 seconds for secondary pelletization and then taken out; by continuously lowering the baffle height (from 100 mm to 30 mm), the granulation-shell material-secondary pelletization steps are repeated, and the granulation and secondary pelletization steps are continuously performed until the granulation is completed. The entire granulation process lasts for 15 minutes.
[0067] (7) All the ceramsite after secondary pelletization is placed in an indoor environment for natural curing for 12 hours, and then moved into a constant temperature and humidity curing room with a temperature of 20±2°C and a relative humidity ≥95%. After curing for 12 hours, it is placed in a steam curing box at a temperature of 90°C for 12 hours, and then allowed to stand at room temperature to obtain fly ash unfired ceramsite.
[0068] Example 8 (1) Weigh 3000 parts of Class F II fly ash dried to constant weight, 300 parts of PO 42.5 ordinary Portland cement, 60 parts of dihydrate gypsum, 75 parts of calcium oxide (analytical grade), 15 parts of sodium silicate powder (analytical grade), 15 parts of sodium hydroxide granules (analytical grade), and 750 parts of water according to mass proportions; weigh 270 parts of Class F II fly ash and 30 parts of PO 42.5 ordinary Portland cement as shell material, and set aside; (2) Pour fly ash, cement and gypsum into a mixer and stir for 60 seconds to obtain a uniform dry mixed material. (3) Pour the weighed sodium silicate powder and sodium hydroxide particles into water and stir continuously in a clockwise direction until they are completely dissolved in water. Then pour the solution into the dry mixed material and stir for 90 seconds to obtain a wet mixed material. Add the weighed calcium oxide and continue stirring for 60 seconds.
[0069] (4) Pour all the materials into the disc granulator, set the disc inclination angle to 50°, the speed to 60r / min, and the baffle height to 30~100mm.
[0070] (5) Place the weighed shell material in a small blender and stir for 60 seconds; (6) After 60 seconds of granulation, the ceramsite matrix is obtained, and the shell material is coated on the surface of the formed ceramsite matrix. The ceramsite matrix is rotated in the granulator for 30 seconds for secondary pelletization and then taken out; by continuously lowering the baffle height (from 100 mm to 30 mm), the granulation-shell material-secondary pelletization steps are repeated, and the granulation and secondary pelletization steps are continuously performed until the granulation is completed. The entire granulation process lasts for 15 minutes.
[0071] (7) All the ceramsite after secondary pelletization is placed in an indoor environment for natural curing for 12 hours, and then moved into a constant temperature and humidity curing room with a temperature of 20±2°C and a relative humidity ≥95%. After curing for 12 hours, it is placed in a steam curing box at a temperature of 90°C for 12 hours, and then allowed to stand at room temperature to obtain fly ash unfired ceramsite.
[0072] Example 9 (1) Weigh 3000 parts of Class F II fly ash dried to constant weight, 300 parts of PO 42.5 ordinary Portland cement, 60 parts of dihydrate gypsum, 75 parts of calcium oxide (analytical grade), 15 parts of sodium silicate powder (analytical grade), 22.5 parts of sodium hydroxide granules (analytical grade), and 750 parts of water according to mass proportions; weigh 270 parts of Class F II fly ash and 30 parts of PO 42.5 ordinary Portland cement as shell materials, and set aside; (2) Pour fly ash, cement and gypsum into a mixer and stir for 60 seconds to obtain a uniform dry mixed material. (3) Pour the weighed sodium silicate powder and sodium hydroxide particles into water and stir continuously in a clockwise direction until they are completely dissolved in water. Then pour the solution into the dry mixed material and stir for 90 seconds to obtain a wet mixed material. Add the weighed calcium oxide and continue stirring for 60 seconds.
[0073] (4) Pour all the materials into the disc granulator, set the disc inclination angle to 50°, the speed to 60r / min, and the baffle height to 30~100mm.
[0074] (5) Place the weighed shell material in a small blender and stir for 60 seconds; (6) After 60 seconds of granulation, the ceramsite matrix is obtained, and the shell material is coated on the surface of the formed ceramsite matrix. The ceramsite matrix is rotated in the granulator for 30 seconds for secondary pelletization and then taken out; by continuously lowering the baffle height (from 100 mm to 30 mm), the granulation-shell material-secondary pelletization steps are repeated, and the granulation and secondary pelletization steps are continuously performed until the granulation is completed. The entire granulation process lasts for 15 minutes.
[0075] (7) All the ceramsite after secondary pelletization is placed in an indoor environment for natural curing for 12 hours, and then moved into a constant temperature and humidity curing room with a temperature of 20±2°C and a relative humidity ≥95%. After curing for 12 hours, it is placed in a steam curing box at a temperature of 90°C for 12 hours, and then allowed to stand at room temperature to obtain fly ash unfired ceramsite.
[0076] Example 10 (1) Weigh 3000 parts of Class F II fly ash dried to constant weight, 300 parts of PO 42.5 ordinary Portland cement, 60 parts of dihydrate gypsum, 75 parts of calcium oxide (analytical grade), 15 parts of sodium silicate powder (analytical grade), 30 parts of sodium hydroxide granules (analytical grade), and 750 parts of water according to mass proportions; weigh 270 parts of Class F II fly ash and 30 parts of PO 42.5 ordinary Portland cement as shell materials, and set aside; (2) Pour fly ash, cement and gypsum into a mixer and stir for 60 seconds to obtain a uniform dry mixed material. (3) Pour the weighed sodium silicate powder and sodium hydroxide particles into water and stir continuously in a clockwise direction until they are completely dissolved in water. Then pour the solution into the dry mixed material and stir for 90 seconds to obtain a wet mixed material. Add the weighed calcium oxide and continue stirring for 60 seconds.
[0077] (4) Pour all the materials into the disc granulator, set the disc inclination angle to 50°, the speed to 60r / min, and the baffle height to 30~100mm.
[0078] (5) Place the weighed shell material in a small blender and stir for 60 seconds; (6) After 60 seconds of granulation, the ceramsite matrix is obtained, and the shell material is coated on the surface of the formed ceramsite matrix. The ceramsite matrix is rotated in the granulator for 30 seconds for secondary pelletization and then taken out; by continuously lowering the baffle height (from 100 mm to 30 mm), the granulation-shell material-secondary pelletization steps are repeated, and the granulation and secondary pelletization steps are continuously performed until the granulation is completed. The entire granulation process lasts for 15 minutes.
[0079] (7) All the ceramsite after secondary pelletization is placed in an indoor environment for natural curing for 12 hours, and then moved into a constant temperature and humidity curing room with a temperature of 20±2°C and a relative humidity ≥95%. After curing for 12 hours, it is placed in a steam curing box at a temperature of 90°C for 12 hours, and then allowed to stand at room temperature to obtain fly ash unfired ceramsite.
[0080] According to the national standard "Lightweight aggregate and its test methods Part 2: Lightweight aggregate test methods" (GB / T17431.2-2010), the performance parameters of comparative examples 1 to 4 and embodiments 1 to 10 are shown in Table 1.
[0081] Table 1 Performance test results of fly ash unburned ceramsite in comparative examples 1 to 4 and examples 1 to 10 Result analysis: From the various properties of conventional fly ash unburned ceramsite in Comparative Examples 1 to 4, it can be seen that a single type of activator cannot fully activate the volcanic ash activity of fly ash, and a single sodium silicate or calcium oxide cannot provide sufficient OH for the system. - , destroying the fly ash glass structure (mainly Si-O-Si and Si-O-Al network structure), less active SiO2 and Al2O3 are dissolved, less CSH and C-(A)-SH gel and crystals such as ettringite are generated in the system, and the density of the internal microstructure is low, resulting in relatively general physical properties of ceramsite, while Comparative Examples 2 and 4 use steam curing, and its high temperature environment can accelerate the dissolution of active substances in fly ash and improve the degree of internal reaction of ceramsite raw balls. At the same time, it is conducive to the water in the system to penetrate layer by layer from outside to inside, increase the number of reaction products, and improve the density of the internal and external structures of raw balls, that is, the performance of Comparative Examples 2 and 4 is better than that of Comparative Examples 1 and 3, respectively. However, due to the lack of active substances inside, the steam curing method has limited effect on the performance of ceramsite. In addition, the method of adding water with a spray bottle causes the powder in contact with water to become slurry first, but the water gradually penetrates into the remaining materials during the rotation process, reducing the water content of the first batch of raw balls, which is not conducive to the internal reaction. At the same time, it increases the water content of subsequent batches of raw balls. The balling process is extremely difficult to control, and the prepared expanded clay is of different sizes and has low strength.
[0082] From the various properties of the fly ash-free ceramsite used in the present invention in Examples 1 to 10, it can be seen that after the fly ash is pretreated with an alkaline solution, calcium is added to significantly improve the volcanic ash activity of the fly ash. At the same time, the method of adding water to stir the material can improve the uniformity of the alkaline excitation of the fly ash, accurately control the amount of water used, and maintain the capillary state (water fills all pores) during the fly ash granulation process. The force on the fly ash particles will discharge the air between the filling particles, and the gaps are filled with water and fly ash particles. There is no water film on the surface of the particles, and the ceramsite raw material balls are pressed more compactly. After that, secondary pelletization is carried out. While the internal structure of the ceramsite raw material balls has a certain stability in the natural curing stage, the shell material quickly hardens to form a hard shell layer, and then in the constant temperature and humidity curing stage, sufficient water is provided, and the error caused by the change of the external environment is reduced, so that the ceramsite matrix and the shell are further reacted, and finally high-temperature steam curing is carried out to provide a high-temperature and high-humidity chemical reaction environment to accelerate the internal chemical reaction of the ceramsite.
[0083] Step by step analysis: From the various properties of the fly ash unburned ceramsite used in Examples 1 to 4 of the present invention, it can be seen that after pretreatment with sodium silicate solution, OH - Under the action of ions, the network structure of the fly ash glass surface is destroyed, the degree of polymerization of the network polymer is greatly reduced, the active SiO2 and Al2O3 are dissolved and separated, and the latent volcanic ash activity of the fly ash is stimulated. The addition of calcium oxide further improves the OH - The amount of Ca 2+ , so that the active oxides react chemically to form gelling substances, thus improving the mechanical properties of ceramsite. It is worth noting that with the increase of the concentration of sodium silicate solution, the cylinder compressive strength of ceramsite first increases and then decreases. When the content of sodium silicate solution is 0.5% by mass of fly ash, the performance of ceramsite is the best, and then gradually decreases. The reason is that the activity of SiO2 in sodium silicate is higher than that in fly ash, and it will react with Ca(OH)2 before fly ash, consuming part of Ca(OH)2 and reducing the strength of ceramsite.
[0084] From the various properties of the fly ash-free ceramsite used in Examples 3, 5, and 6 of the present invention, it can be seen that the performance of the ceramsite improves with the increase of the calcium oxide content. The calcium oxide reacts with water to release heat, which can further improve the activity of the fly ash during the stirring stage. In addition, it can provide sufficient Ca for the system. 2+ With OH - Equal reaction substances, in OH - Under the action of Ca 2+ It can promote the formation of CSH gel in the gelling system.
[0085] From the various properties of the fly ash unfired ceramsite used in Examples 7 to 10 of the present invention, it can be seen that the addition of sodium hydroxide further enhances the activity of the fly ash, promotes the degree of reaction inside the ceramsite, and significantly improves the comprehensive performance of the fly ash unfired ceramsite. In the alkaline environment of the system, most of the glass of the fly ash is corroded, the depolymerization ability is strong, and a large amount of active SiO2 and Al2O3 are dissolved, and a hydration reaction occurs to form a gelling substance, and the strength is increased. In addition, the main component of gypsum in the system is CaSO4, and fly ash in SO4 2- With Ca 2+ Under the dual effects of , it reacts with active Al2O3 to form hydrated calcium sulphoaluminate (ettringite), which improves the strength of ceramsite.
[0086] The main chemical reactions involved are: Conclusion: Compared with conventional fly ash unfired ceramsite, the preparation method provided by the present invention can not only accurately control the water consumption, maintain the capillary state during the fly ash granulation process, and improve the density of the ceramsite raw material ball, but also fully stimulate the volcanic ash activity of fly ash. Even at low cement content, more active substances such as active SiO2 and Al2O3 can be dissolved and precipitated, and a large amount of gels such as CSH and C-(A)-SH and crystals such as ettringite can be generated, which significantly improves the performance of ceramsite. Examples 1 to 10 of the fly ash unfired ceramsite prepared by the present invention all show excellent performance, with a cylinder pressure strength of 6.53 to 8.98 MPa, a water absorption rate of 12.53% to 17.24%, and a bulk density of 810.84 to 857.24 kg·m -3 , the apparent density is 1412.24~1667.46 kg·m -3 The softening coefficient is 0.82~0.92, which meets the relevant requirements of 900-grade high-strength light coarse aggregate in the national standard "Light Aggregate and Its Test Methods Part 1: Light Aggregate" (GB / T17431.2-2010), making the present invention applicable to the field of lightweight structural concrete.
[0087] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A method for preparing fly ash unburned ceramsite, characterized in that: The fly ash unburned ceramsite is granulated to obtain a ceramsite matrix, which is then subjected to secondary pelletization to construct a shell structure and is obtained after a composite curing method; the ceramsite matrix is prepared from fly ash, cement, gypsum, an alkali activator and water, wherein the fly ash accounts for 86.2wt% to 90.9wt% of the total dry material, cement accounts for 10% of the fly ash mass, gypsum accounts for 2% of the fly ash mass, the alkali activator accounts for 2% to 5% of the fly ash mass, and the water addition amount is 25% of the fly ash mass; the shell is made of fly ash and cement, and the total shell material is 10% of the fly ash mass used for the ceramsite matrix.
2. The method for preparing fly ash unburned ceramsite according to claim 1, characterized in that: The equipment used for granulation is a disc granulator with a diameter of 600 mm.
3. The method for preparing fly ash unburned ceramsite according to claim 1, characterized in that: The fly ash is of Class II F, the cement is ordinary Portland cement with a model of PO 42.5, and the gypsum is dihydrate gypsum.
4. The method for preparing fly ash unburned ceramsite according to claim 1, characterized in that: The alkaline activator is composed of calcium oxide, sodium silicate and sodium hydroxide, all of which are pure chemical reagents. The calcium oxide content is 2% to 3% of the mass of the fly ash, the sodium silicate content is 0.25% to 1% of the mass of the fly ash, and the sodium hydroxide content is 0.25% to 1% of the mass of the fly ash. The fly ash used in the shell accounts for 90wt% of the shell material, and cement accounts for 10wt% of the shell material.
5. The method for preparing fly ash unburned ceramsite according to claim 1, characterized in that: The water is added after the materials are dry-mixed evenly.
6. The method for preparing fly ash unburned ceramsite according to claim 1, characterized in that: The composite curing is a combination of natural curing, constant temperature and humidity curing and steam curing, which are carried out in sequence, and the three curing times are all 12 hours.
7. The method for preparing fly ash unburned ceramsite according to claim 1, characterized in that: The following steps are involved: (1) Dry the fly ash to constant weight and weigh the raw materials according to the proportion; (2) Pour fly ash, cement and gypsum into a mixer and stir for 60 seconds to obtain a uniform dry mixed material; (3) Pour sodium hydroxide and sodium silicate into water, stir continuously in a clockwise direction until completely dissolved in water, then pour the solution into the dry mixed material, stir for 90 seconds, obtain a wet mixed material, add calcium oxide, and continue stirring for 60 seconds; (4) Pour all materials into the disc granulator, set the disc inclination angle to 50°, the speed to 60r / min, and the baffle height to 30~100mm; (5) After 60 seconds of granulation, a ceramsite matrix is obtained, and the shell material is sprinkled on the surface of the ceramsite matrix, and the ceramsite matrix is rotated in the granulator for 30 seconds for secondary pelletization and then taken out; by continuously lowering the baffle height from 100 mm to 30 mm, the granulation-sprinkling shell material-secondary pelletization steps are repeated, and the granulation and secondary pelletization steps are continuously performed until the granulation is completed; (6) All the ceramsite after secondary pelletization was placed in an indoor environment for 12 hours for natural curing, and then moved into a constant temperature and humidity curing room with a temperature of 20±2°C and a relative humidity of ≥95%. After curing for 12 hours, it was placed in a steam curing box at a temperature of 90°C for 12 hours. After standing to room temperature, fly ash unfired ceramsite was obtained.
8. The fly ash unburned ceramsite obtained by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Preparation method of alkali-activated fly ash decoration mortar
CN106380146A
Preparation method of baking-free high-strength fly ash ceramsite
CN111205061A
Preparation method of autoclaved lightweight high-strength high-fly-ash-content ceramsite
CN112250334A
Fly ash solid waste fiber unfired ceramsite and manufacturing method therefor
WO2021217784A1
Cited By
High-strength early-strength water-resistant artificial muck aggregate based on alkali excitation and cold-bonding granulation process and preparation method of high-strength early-strength water-resistant artificial muck aggregate
CN120192144A
High-strength fracturing propping agent for oil and gas wells and preparation method of fracturing propping agent
CN120349786A
Preparation method of small-particle-size ceramsite for sound absorption material of sound barrier
CN120554091A
Microorganism-gel synergistically reinforced fly ash ceramsite and preparation method thereof
CN121494452A
